Analysis of Karate Athletes' Emotional Intelligence and its Relationship to Competition Performance - Risma Prescilia Rahmatilah; Muhammad Nur Alif; Anggi Setia Lengkana (Tadulako Journal Sport Sciences And Physical Education, 2026)
The high cognitive and emotional demands in martial arts, particularly in karate competitions, create intense psychological pressure that requires athletes to regulate their emotions effectively, making emotional intelligence a crucial mechanism that protects athletes from anxiety and performance decline while enabling them to maintain focus, control techniques, and make accurate decisions during matches. This study aims to analyze the dynamics of karate athletes' emotional intelligence and its relationship with performance in competitive situations. This study uses a qualitative approach with a case study design involving six athletes and two coaches. Data collection was conducted through observation, semi-structured interviews, questionnaires, and documentation, then analyzed using NVivo to identify themes and conceptual relationships. The results show that emotional intelligence, which includes emotional awareness, emotional control, and self-motivation, plays a significant role in maintaining the stability of athletes' performance during competitions. Data visualization reveals that competitive pressure is multidimensional, including nervousness, pressure, frustration, worry, and fear. Athletes with good emotional regulation skills tend to be better at managing anxiety, maintaining focus, and maintaining the quality of their techniques and decision-making. These findings confirm that emotional intelligence functions as a protective mechanism against performance decline due to match pressure. Therefore, the development of emotional intelligence needs to be systematically integrated into karate athlete training programs to support long-term performance consistency.